Lipid peroxidation is not associated with adipocytokines in preeclamptic women - Ali Khosrowbeygi; Nahid Lorzadeh; Hassan Ahmadvand (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: The association between lipid peroxidation biomarkers and adipocytokines is hypothesized in preeclampsia but little is known about it.Objective: The present study was undertaken to determine the association of lipid peroxidation biomarkers measured by the levels of 8-isoprostane and malondialdehyde with adipocytokines leptin and adiponectin in maternal serum of preeclamptic women.Materials and Methods: A cross-sectional study was designed. The study population consisted of 30 preeclamptic patients and 30 healthy pregnant women. Serum levels of 8-Isoprostane, total leptin and total adiponectin were assessed using commercially available enzyme-linked immunosorbent assay methods. The amount of malondialdehyde was determined by the thiobarbituric acid assay. Mann-Whitney U test and Spearman's correlation coefficient were used for statistical analysis.Results: Both 8-Isoprostane and malondialdehyde were significantly higher in preeclamptic group than those in normal pregnant women. Serum levels of leptin were significantly increased in preeclamptic patients compared with normal group, while adiponectin levels were decreased. Serum levels of 8-Isoprostane and malondialdehyde did not show any significant correlation with leptin and adiponectin.Conclusion: In preeclamptic women, maternal serum levels of leptin and adiponectin were not correlated with lipid peroxidation.